The life of an English teacher: Motivation strategies and aid - Nafiah, Silvia Umrotun; Sugirin; Putro, Nur Hidayanto Pancoro Setyo (Indonesian Research Journal in Education |IRJE|, 2025)
The nature of young learners differs from that of teenagers and adults, necessitating their teachers’ use of specific tactics to stimulate their motivation to acquire English proficiency effectively. The Aksi Inspirasi Indonesia community in Yogyakarta witnessed the manifestation of motivated behaviors in youngsters, including heightened attention and active engagement in learning. Hence, this research aims to delineate the motivational tactics English instructors employ in the Aksi Inspirasi Indonesia community when instructing young learners. The study employs a qualitative methodology, with case studies as its primary technique. Data collection involves the utilization of observation, interviews, and documentation. Research findings indicate that two tutors from the Aksi Inspirasi Indonesia community employ four characteristics of motivational methods in their English instruction, as proposed by Dörnyei. They establish fundamental motivational circumstances, provide initial drive, sustain and safeguard motivation, and promote positive reflective self-assessment. These tactics are utilized in learning to address, maintain, and enhance their motivation.